Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If $a_1,a_2,\dots,a_n,b_1,b_2,\dots,b_n$ are complex numbers in $\mathbb C$, and for every $j\in\mathbb N$, we have the power sums $$\sum_{i=1}^n a_i^j=\sum_{i=1}^n b_i^j$$ I want, without applying the Newton's identities to prove that $a_i$ is just $b_k$ with proper subscripts order.

share|cite|improve this question
Why? Newton's identities are a completely transparent proof of this. – Qiaochu Yuan Sep 23 '11 at 1:03
up vote 4 down vote accepted

We prove this by induction on $n$, the case where $n=1$ being trivial. Without loss of generality, you can assume $b_1$ has the largest magnitude of all the $a_i$'s and $b_i$'s (otherwise just change the names around). Dividing each $a_i$ and each $b_i$ by $b_1$, we may assume $b_1 = 1$.

Adding the equations $\sum_{i = 1}^n a_i^j = \sum_{i = 1}^n b_i^j$ from $j = 1$ to $j = m$ for some $m$ and then dividing by $m$, you obtain $$\sum_{i=1}^n {1 \over m}\sum_{j=1}^{m}a_i^j = \sum_{i=1}^n {1 \over m}\sum_{j=1}^{m}a_i^j$$ Let $k$ denote the number of $a_i$'s equal to $1$, and let $l$ denote the number of $b_i$'s equal to $1$. By the formula for summing geometric series you get $$k + \sum_{\{i: a_i \neq 1\}} {1 \over m} {a_i^{m+1} - a_i \over a_i - 1} = l + \sum_{\{i: b_i \neq 1\}} {1 \over m} {b_i^{m+1} - b_i \over b_i - 1}$$ Now taking the limit of the above as $m$ goes to infinity (recalling each $|a_i|$ and $|b_i|$ are at most $1$) you get that $k = l$. This means that $k$ of the $a_i$'s are equal to $k$ of the $b_i$'s (and are all equal to 1). Thus we can remove them from the sums, and it remains to consider the remaining $n - k$ $a_i$'s and $n -k$ $b_i$'s. The result follows by induction and we're done.

share|cite|improve this answer
$\max|a_i|=\max|b_i|$, right? – gylns Sep 23 '11 at 3:04
That follows from that $k = l$ since $l$ is at least 1. And it follows from the overall statement of course too. – Zarrax Sep 23 '11 at 3:35

Let $A$ and $B$ be the sets $\{a_j\}_{j=1}^n$ and $\{b_j\}_{j=1}^n$ respectively. Note that $\sum_{j=1}^n p(a_j) = \sum_{j=1}^n p(b_j)$ for all polynomials $p$. Now for any $\alpha \in A \cup B$ we have a polynomial $p(z) = \prod \{\frac{z - c}{\alpha - c}: c \in A \cup B \backslash \{\alpha\}\}$ such that $p(\alpha) = 1$ but $p(c) = 0$ for all other $c \in A \cup B$. So $\sum_{j=1}^n p(a_j)$ is the number of times $\alpha$ occurs in the sequence $(a_j)_{j=1}^n$, and this is the same as $\sum_{j=1}^n p(b_j)$ which is the number of times $\alpha$ occurs in $(b_j)_{j=1}^n$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.